Enhancement of Corrosion Resistance AISI 304 Steel by Plasma Polymerized Thin Films - Santos, Nazir M. [UNESP]; Amorim, Jayr; Nascente, Pedro A.p.; Freire, Célia M.a.; Cruz, Nilson C. [UNESP]; Rangel, Elidiane Cipriano [UNESP] (Springer Nature, 2013)
The purpose of this work is the deposition of films in order to increase the corrosion resistance of AISI 304 steel, which is a material used to construct the reactors for bioethanol production. This deposition inhibits the permeation of corrosive species to the film-metal interface. Thin films were prepared by radio-frequency plasma enhanced chemical vapor deposition (RF-PECVD) method using plasmas of hexamethyldisiloxane/argon/oxygen mixtures excited by signals of different powers. The plasma was generated by the application of RF power of 13.56 MHz to the sample holder while keeping grounded the topmost electrode and the chamber walls. The effect of the RF power on the properties of the samples was investigated by perfilometry, X-ray photoelectron spectroscopy (XPS), contact angle, and electrochemical impedance spectroscopy (EIS). The results of the corrosion resistance tests of the AISI 304 steel were interpreted in terms of the energy delivered to the growing layer by plasma excitation power.
Keywords: Corrosion resistance; HMDSO; Organosilicon films; PECVD